2013
DOI: 10.1089/cell.2013.0001
|View full text |Cite
|
Sign up to set email alerts
|

Alternating Current Electric Fields of Varying Frequencies: Effects on Proliferation and Differentiation of Porcine Neural Progenitor Cells

Abstract: Application of sinusoidal electric fields (EFs) has been observed to affect cellular processes, including alignment, proliferation, and differentiation. In the present study, we applied low-frequency alternating current (AC) EFs to porcine neural progenitor cells (pNPCs) and investigated the effects on cell patterning, proliferation, and differentiation. pNPCs were grown directly on interdigitated electrodes (IDEs) localizing the EFs to a region accessible visually for fluorescence-based assays. Cultures of pN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 40 publications
3
29
0
Order By: Relevance
“…Lim J. H. et al found a beneficial effect of EMF exerted by the frequencies 10 Hz and 50 Hz on the culture of stem cell lines collected from swine [50]. A similar phenomenon was observed by Liu C. et al in the case of cell culture lines of mesenchymal cells of rat bone marrow stroma [51].…”
Section: Mechanisms Of the Effect Of Emrsupporting
confidence: 61%
“…Lim J. H. et al found a beneficial effect of EMF exerted by the frequencies 10 Hz and 50 Hz on the culture of stem cell lines collected from swine [50]. A similar phenomenon was observed by Liu C. et al in the case of cell culture lines of mesenchymal cells of rat bone marrow stroma [51].…”
Section: Mechanisms Of the Effect Of Emrsupporting
confidence: 61%
“…For example, Ariza et al found out that AC did not have a negative impact on viability versus DC which had a destructive effect on the viability of hippocampal neural progenitor cells (NPCs) . In another study, researchers used a series of AC currents (1‐10‐50 Hz) to investigate the viability and differentiation of stem cells and finally discovered that none of these AC currents affect the cell viability in 7 days . In our study, we stimulated CJMSCs using AC current with frequencies 1 and 100 Hz.…”
Section: Discussionmentioning
confidence: 86%
“…74 In another study, researchers used a series of AC currents (1-10-50 Hz) to investigate the viability and differentiation of stem cells and finally discovered that none of these AC currents affect the cell viability in 7 days. 18 In our study, we stimulated CJMSCs using AC current with frequencies 1 and 100 Hz. However, the result shows that 1-Hz frequency has more cytotoxicity than 100 Hz.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IDEs were connected to a signal generator (33220A; Agilent Technologies, Santa Clara, CA, USA). Stimulus intensity of 10 mV (peak‐to‐peak) was used to generate the calculated electrical fields of 1 V/cm on cells (12, 38). Waveform and intensity were confirmed with an oscilloscope.…”
Section: Methodsmentioning
confidence: 99%